The (Un)Clear Effects of Invalid Retro-Cues - Gressmann, Marcel; Janczyk, Markus (Frontiers in Psychology, 2016)
Studies with the retro-cue paradigm have shown that validly cueing objects in visual working memory long after encoding can still benefit performance on subsequent change detection tasks. With regard to the effects of invalid cues, the literature is less clear. Some studies reported costs, others did not. We here revisit two recent studies that made interesting suggestions concerning invalid retro-cues: One study suggested that costs only occur for larger set sizes, and another study suggested that inclusion of invalid retro-cues diminishes the retro-cue benefit. New data from one experiment and a reanalysis of published data are provided to address these conclusions. The new data clearly show costs (and benefits) that were independent of set size, and the reanalysis suggests no influence of the inclusion of invalid retro-cues on the retro-cue benefit. Thus, previous interpretations may be taken with some caution at present.